Legal protection for workers ' rights in the Indonesian labor system - Lieke Ayu Amelia (The International Journal of Politics and Sociology Research, 2023)
In every company, always strives to create a cooperative and comfortable work environment for every employee. However, it is not uncommon for disputes or conflicts to occur in a company due to differences of opinion or matters that are not in accordance with the regulations in force in Indonesia. When a dispute occurs, sometimes employees need representatives to convey their aspirations or act on behalf of employees. With the existence of a workers' in a company, it is intended for all aspirations will be better conveyed and create a harmonious relationship between the Company and employees. Many companies currently have labor s to improve the welfare of workers, including when there is a dispute over work relations whether it ends in termination of employment or not. The Research Methods used are normative research techniques, this paper is intended to discuss the role of trade, especially those that have an impact on termination of employment.The results of the research obtained are Labor law was born from the idea of providing protection for parties, especially workers as weak parties and social justice in labor relations between parties who have considerable similarities and differences. The goal of social justice in the field of labor can be realized one way is by protecting workers against unlimited power on the part of employers, through existing legal means.